PENGARUH SALES PROMOTION DAN PERSONAL SELLING TERHADAP CUSTOMER RETENTION PENGGUNA INDIHOME DI PT TELKOM KANTOR CABANG UJUNG BERUNG BANDUNG - Hening Pratiwi; Wulan Yuliyana; Yunika Komalasari; Feti Fatimah Maulyan (Jurnal Sains Manajemen, 2022)
ABSTRACT Indihome (Indonesia Digital Home) is a triple play service from PT Telkom products in the form of an information telecommunications service package.Customer retention is a sales activity carried out by an organization in retaining customers. The purpose of this research was to determine how the effect of sales promotion and personal selling to customer retention of Indihome users at PT Telkom Ujung Berung Branch Office Bandung. The sample used in this research were 100 respondents with a non probability sampling technique. The data obtained were analyzed using SPSS version 20 and the techniques of data analysis used descriptive and verification method.The result of research concluded that both has a positive and significant effect in customer retention. Simultaneously sales promotion and personal selling significant influence the customer retention.